Contributions of Positive Psychology in Self-Regulated Learning: A Study With Brazilian Undergraduate Students - Kaiser, Vanessa; Reppold, Caroline Tozzi; Hutz, Claudio Simon; Almeida, Leandro S. (Frontiers in Psychology, 2020)
Self-regulated learning (SRL) is an important factor for academic success. The present study aimed to investigate the relationship between constructs typical of positive psychology (PP) (self-esteem, self-efficacy, affects, life satisfaction, optimism, and hope) and SRL while indicating the explained variance of these constructs in an SRL model. The study comprised 1,046 undergraduate students from 63 public higher education institutions from all demographic regions of Brazil. Significant correlations (p < 0.01) were found between SRL and all PP variables. Moderate correlations were found with self-efficacy and positive affects. The linear regression analysis indicated that one model explains 41.9% of the variance in SRL. The data are discussed based on the potential of PP and SRL interventions to improve academic performance and student adaptation to higher education environments.